Penerapan Model Problem Based Learning Untuk Meningkatkan Literasi Ekonomi Peserta Didik - Rosmayanti (CV. SINAR HOWUHOWU, 2025)
This research was prompted by the low level of economic literacy among students, often attributed to the dominance of passive, conventional teaching methods. This study aims to enhance the economic literacy of eleventh-grade Social Studies students through the implementation of the Problem-Based Learning (PBL) model. This study employed a Classroom Action Research (CAR) design conducted in two cycles, with each cycle comprising the stages of planning, action, observation, and reflection. The subjects of the research were 32 students at a public senior high school in Medan. Data were collected using tests to measure economic literacy and observation sheets to monitor learning activities. The findings revealed a significant improvement. The classical mastery learning percentage for students increased from a baseline of 21.8% to 56.25% in Cycle I, ultimately reaching 90.6% at the end of Cycle II. Furthermore, a positive increase in student activity and participation was observed throughout the learning process. Based on these findings, it is concluded that the application of the Problem-Based Learning model can effectively enhance students' economic literacy.